Why Only Focus on One Variety of English? A Problem in EIL Teaching in Vietnam - Hang Thi Nhu Mai (Journal of English Language Teaching and Linguistics, 2017)
Although research has proposed the urgent need of exposing learners to World Englishes for enhancing learners’ intercultural competence, Standard English, which is either British English or American English, still remains dominant in English language classrooms in the Vietnamese context. This qualitative-designed case study aims to explore Vietnamese higher-education teachers’ explanations for the reasons behind and their perspectives towards embracing World Englishes in English language classrooms. The study employed semi-structured interviews to collect data from five Vietnamese lecturers. The participants’ answers were recorded before being converted into an Excel sheet. A Coding Process of Inductive Analysis (Cresswell, 2002) was adapted to analyze data. The results indicated that the factors including fixed materials, limited classroom time, teachers’ previous training in Standard English (SE) for their degrees, and learners’ favor of SE accounted for the main use of Standard English in language classrooms. Interestingly, however, all of the participants agreed that increasing knowledge of World Englishes is substantially necessary for successful intercultural communications. Moreover, learners are supposed to keep their identity in international encounters through their own English accents while still ensuring mutual intelligibility. The study drew on an implication for teachers to take an active role as transformative intellectuals in classrooms to make the EFL teaching process meet Vietnamese learners’ goals and needs.